Inventory and Mapping of Disability-Owned Micro, Small, and Medium Enterprises (MSMEs) as a Strategy to Strengthen Inclusive Economic Development in Bekasi City : A Descriptive Qualitative Study - Milda Handayani; Ricca Handayani; Muhammad Richo Rianto (Draf Solusi Indonesia, 2025)
This study explores the inventory and mapping of disability-owned Micro, Small, and Medium Enterprises (MSMEs) in Bekasi City as a strategy to strengthen inclusive local economies. Using a descriptive qualitative approach, the research identified 110 MSMEs, with the majority engaged in traditional (25.5%) and modern food sectors (21.8%), reflecting the accessibility and market potential of the culinary industry for persons with disabilities. Other enterprises such as tailoring, massage, and handicrafts highlight their diverse skills and adaptability. Most operate independently with family support, yet face challenges in access to capital, training, and digital marketing. The study emphasizes the need for stronger collaboration among government, social institutions, and the private sector to develop an inclusive entrepreneurial ecosystem that fosters empowerment and economic participation of persons with disabilities.